2013
DOI: 10.1080/00405000.2013.829687
|View full text |Cite
|
Sign up to set email alerts
|

Vibrations, quanta and biology

Abstract: Quantum biology is an emerging field of research that concerns itself with the experimental and theoretical exploration of non-trivial quantum phenomena in biological systems. In this tutorial overview we aim to bring out fundamental assumptions and questions in the field, identify basic design principles and develop a key underlying theme -the dynamics of quantum dynamical networks in the presence of an environment and the fruitful interplay that the two may enter. At the hand of three biological phenomena wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
532
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 561 publications
(540 citation statements)
references
References 174 publications
(244 reference statements)
6
532
0
2
Order By: Relevance
“…The same conclusion was also drawn from an experiment at higher temperatures up to 4 • C (4), and similar beatings have been reported for marine cryptophyte algae (5) as well. These experiments have triggered an enormous interest in a potential new field of "quantum biology" (10)(11)(12)(13)(14), with far-reaching consequences, even for the functionality of the human brain (15) and for technological applications (16). The cornerstone experiments (3-5) remained unconfirmed until recently, when a new effort was made to identify the excitonic energy transfer pathways (17) at 77 K. However, observation of long-lived electronic coherences in the 2D off-diagonal signals was not mentioned in ref.…”
Section: Significancementioning
confidence: 99%
“…The same conclusion was also drawn from an experiment at higher temperatures up to 4 • C (4), and similar beatings have been reported for marine cryptophyte algae (5) as well. These experiments have triggered an enormous interest in a potential new field of "quantum biology" (10)(11)(12)(13)(14), with far-reaching consequences, even for the functionality of the human brain (15) and for technological applications (16). The cornerstone experiments (3-5) remained unconfirmed until recently, when a new effort was made to identify the excitonic energy transfer pathways (17) at 77 K. However, observation of long-lived electronic coherences in the 2D off-diagonal signals was not mentioned in ref.…”
Section: Significancementioning
confidence: 99%
“…20 Furthermore, extensive work has been carried out to investigate the efficiency and robustness of the FennaMatthews-Olson (FMO) PPC with respect to fluctuations in the protein environment, with findings showing that thermal fluctuations can enhance EET via so-called environmentassisted quantum transport (ENAQT). [21][22][23][24][25][26] Similar studies of photosynthetic systems have investigated EET efficiency optimisation with respect to environmental model parameters such as temperature or exciton trapping rates. 6,20,21,27,28 The effect of removing a chromophore on EET efficiency has also been investigated, and it has been suggested that photosynthetic EET networks display a robustness to the loss of a chromophore in the network through the utilisation of multiple EET pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, Einstein was not happy with a quantum jargon mixing wave and particle elements and was sure that wave-particle duality should be finally resolved in favor of a wave model perse. Indeed nowadays quantum biological effects at room temperature have been discovered (reviewed by Arndt et al, 2009;Ball, 2011;Lambert et al, 2013;Lloyd, 2014;Huelga and Plenio, 2013). …”
Section: Introductionmentioning
confidence: 99%